Primary Cutaneous Versus Salivary Gland Origin Mucoepidermoid Carcinoma. (March 2015) - Yu, Ryan; Salama, Samih; Alowami, Salem
Abstract : Abstract: Mucoepidermoid carcinoma (MEC) is a malignant glandular epithelial neoplasm that most commonly arises in the major salivary glands. Primary cutaneous MEC is very rare. There is a particular diagnostic challenge in determining the primary site of MEC when it is found in skin overlying the parotid gland. Attention to a combination of morphologic findings may be helpful. However, differentiation of primary cutaneous MEC from secondary cutaneous involvement by a parotid MEC may be unnecessary once the parotid gland is infiltrated. We report the case of a 54-year-old male with a 2-cm asymptomatic mass overlying the right parotid gland, which was managed by excision of the affected skin, right total parotidectomy, and right neck dissection. Histopathologic and immunohistochemical findings were consistent with a cutaneous intermediate-grade MEC. Postoperative radiotherapy was deferred. The patient showed no evidence of recurrence or metastasis at 2 months before self-discontinuing follow-up. To our knowledge, this is only the second reported case of MEC involving the parotid gland, but of overlying primary cutaneous origin.